Global Assessment of Urological Endoscopic Skills (GAUES): development and validation of a novel assessment tool to evaluate endourological skills. (14th October 2020) - Biyani, Chandra Shekhar; Kailavasan, Mithun; Rukin, Nicholas; Palit, Victor; Somani, Bhaskar; Jain, Sunjay; Myatt, Andy; Nabi, Ghulam; Patterson, Jake
Abstract : Objective: To develop and evaluate an assessment tool for endourological skills during simulation including cystoscopy, ureteroscopy (URS) and transurethral resection (TUR) procedures. Methods: We designed a Global Assessment of Urological Endoscopic Skills (GAUES) tool, comprised of nine endourology task‐specific and two global‐rating skills items. The tool was developed through two rounds of the Delphi process. The GAUES tool was used to assess acquisition of URS and TUR skills of novices (Year 2 core surgical trainees, CT2) and intermediate level trainees (residents at the start of the UK higher surgical training programme in Urology, Speciality Trainee Year 3, ST3) at the Urology Simulation Boot Camp (USBC) between 2016 and 2018. Validity was evaluated by comparing scores between trainees with different levels of urological experience. Inter‐rater reliability was also assessed. Results: We evaluated 130 residents, 52% of trainees were at an intermediate stage of training and 39% were novices. In all, 9% of the anonymous forms were missing demographics. The completion rate of the GAUES tool during the USBC for URS and TUR was 85% and 89%, respectively. Our analysis demonstrated a significant difference in all domains between intermediates and novices at assessment in URS, except for one domain more suited to clinical assessment ( P  = 0.226). There was excellent intraclass correlation (ICC) overall between the two experts' judgements, ICC = 0.841 (95% confidence interval 0.767–0.893; P  < 0.001, n  = 88). Conclusions: We have developed the novel GAUES tool for cystoscopic, URS and TUR skills. Overall, we demonstrated good face, content and construct validity and excellent reliability, suggesting that the GAUES tool can be useful for endourological skills assessment.